Integrated Buddhist Administration for Excellence - ปภสฺสโร พระครูโกศลพัฒนาภรณ์ (Journal of Educational Review Faculty of Education in MCU, 2018)
Administration is important in every organization. The school administration is the key potential to produce good, qualified and happy students in living a life. Buddhist principle has an important role in helping school administrators to administrate their schools effectively. School administrators need to have Buddhist principles in school administration for the ideal of teachers, students and their parents. Integration of Buddhist principles in the administration is in need for all executives in school administration.